2020
DOI: 10.3390/su12229480
|View full text |Cite
|
Sign up to set email alerts
|

Transport Mode Choice for Residents in a Tourist Destination: The Long Road to Sustainability (the Case of Mallorca, Spain)

Abstract: Sustainable mobility policies may encounter social, economic, and cultural barriers to successful implementation that need to be assessed. In this sense, knowledge of the population’s mobility habits and their relationship with transport modes is particularly essential. Along these lines, a study was carried out of the patterns of transport modes chosen concerning various social and territorial variables on the island of Mallorca based on the most recent mobility surveys. The study shows that the choice of mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 75 publications
0
9
0
Order By: Relevance
“…In this approach, it is interesting to consider the work of Parra-López and Martínez González [114]. The study of the lines of tourism research developed in island environ ments shows the need for these issues to be extensively analyzed in these environment Although most of the lines of research detected have been included in our study, the sin gularity of island environments is evident, and the complementarity of both studies i confirmed.…”
mentioning
confidence: 61%
“…In this approach, it is interesting to consider the work of Parra-López and Martínez González [114]. The study of the lines of tourism research developed in island environ ments shows the need for these issues to be extensively analyzed in these environment Although most of the lines of research detected have been included in our study, the sin gularity of island environments is evident, and the complementarity of both studies i confirmed.…”
mentioning
confidence: 61%
“…Discrete choice model applications provide a good degree of predictability of user behavior and, therefore, have been widely used in the area of transport demand for decades [4,5,6,7,8,9,10,11]. These models make use of data obtained from Revealed Preference (RP) and Stated Preference (SP) techniques, in which the RP data represent choices effectively made by individuals and the SP data refer to choices considering a set of options in which hypothetical scenarios are presented to the consumer for him/her to indicate his/her option [12,13].…”
Section: Discrete Choice Models and Revealed And Stated Preference Su...mentioning
confidence: 99%
“…In addition, the adverse impact of unexpected events, e.g., natural disasters [1][2][3], terrorist attacks [4], severe climates [5], the COVID-19 pandemic, and major accidents [6], on RTNs is also becoming increasingly serious. Damaged RTNs decrease travel efficiency and result in significant societal economic losses during grid disturbances [7]. The capacity of RTNs to actively adapt in response to these unexpected events is called resilience [8].…”
Section: Introductionmentioning
confidence: 99%